103k views
4 votes
Pleaseee answer correctly !!!!!!!!!! Will mark Brianliest !!!!!!!!!!!!!!!

Pleaseee answer correctly !!!!!!!!!! Will mark Brianliest !!!!!!!!!!!!!!!-example-1
User Jirka
by
4.2k points

2 Answers

4 votes

Answer:


2√(13)

Explanation:

Lets call the axes x and y.

Distance in x axis is (9 - 5) = 4

Distance in y axis (3 - (-3)) = 6

The total distance is
√(4^2 + 6^2) = √(16 + 36) = √(52) = √(4 \cdot 13) = 2√(13)

User Repcak
by
4.9k points
13 votes

Answer:

2 sqrt(13)

Explanation:

We can use the distance formula

d =sqrt( ( x2-x1)^2 + (y2-y1)^2)

=sqrt( (-3-3)^2 + ( 5-9)^2)

= sqrt( (-6)^2 + (-4) ^2)

= sqrt( 36+ 16)

= sqrt( 52)

= sqrt (4 * 13)

= 2 sqrt(13)

User Andrew Kovalenko
by
4.5k points